Investigation of the Adjustment of the Eskimos at Barter Island, Alaska to Rapid Cultural Changes - Chance, Norman A. (ARCTIC, 1960)
The main objective of the field work carried out in March-April 1960 was the testing of a method that will make possible a relatively quick survey of the physical and mental health in an Eskimo community like that on Barter Island. After discussions with health survey specialists at the Harvard School of Public Health, the Cornell Medical Index Questionnaire (CMI) was chosen as the main instrument to be tried out in the field. The CMI contains 195 questions and was originally devised to collect a large body of medical and psychiatric data from American patients in a minimal amount of time. Revision of the questionnaire, necessary to meet the educational and cultural differences present in the village, was accomplished in consultation with various public and mental health specialists familiar with Eskimo concepts of health and disease. Following a preliminary test at Barrow, the final form of the CMI was administered to the Barter Island Eskimos by three specially trained native interviewers. A 91 per cent sample of all adults over the age of seventeen (n=51) was obtained. The results were then briefly compared with some of the medical records of the sample population at the native hospital at Barrow. While it is hoped that a much more thorough comparative analysis can be made during the summer of 1961, the preliminary findings suggest that the questionnaire can be used profitably in a non-western cultural setting. In the relatively few instances in which individual responses indicate a strong cultural bias, anthropological knowledge can be used to interpret the results correctly. For example, questions about difficulties in making decisions (as an index of "inadequacy") were answered positively by a large majority of Eskimo women. In view of the passive role played by women in this society, a resolute woman should be considered deviant rather than adequate. Further analysis of the questionnaire should contribute additional knowledge to the whole area of cross-cultural health testing. The general anthropological ...